Pengaruh lingkungan Kerja dan Kompensasi Terhadap Kinerja Pegawai Aparatur Sipil Negara pada Kantor Zeni Daerah Militer (ZIDAM) XIV/Hasanuddin Makassar. - Sitti Aisyah Syafni Rukka; Sadariah Sadariah (LPPM STIE Tri Dharma Nusantara - Makassar, 2026)
This study aims to analyze the influence of the work environment and compensation on the performance of Civil Servants (ASN) at the Military Regional Engineering Office (ZIDAM) XIV/Hasanuddin Makassar. This study used a quantitative approach with primary data sources obtained through questionnaires distributed to all ASN at the ZIDAM XIV/Hasanuddin Makassar Office using a saturated sampling technique. Data analysis was conducted through descriptive analysis, data quality testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and correlation coefficient and determination analysis. The results indicate that the work environment has a positive and significant effect on employee performance. Compensation also has a positive and significant impact on employee performance and is a variable that contributes more significantly than the work environment. Simultaneously, the work environment and compensation have a positive and significant impact on employee performance, making both important factors in supporting the improvement of civil servant performance at the ZIDAM XIV/Hasanuddin Makassar Office.